Insecurity and School Environment as predictors of Psychological Behaviour of Students in Tertiary Institutions in South East Nigeria - Enwere, Chinwe Augustina (Teaching, Learning, and Development, 2026)
In recent years, insecurity has emerged as a significant challenge in tertiary institutions across South East Nigeria, negatively affecting students’ academic performance, psychological well-being, and overall campus experience. Reports of kidnapping, cult activities, armed robbery, and inadequate security measures have heightened students’ fear and anxiety, leading to emotional stress, reduced concentration, and withdrawal from social and academic activities. The study employed a descriptive survey design. A multi-stage sampling technique produced a sample of 3,000 students (1,812 males and 1,188 females). Data were collected using a validated structured questionnaire covering demographics, insecurity experiences, psychological behaviour, and school environment. Responses were measured on a four-point Likert scale. Data analysis involved frequencies, percentages, means, and standard deviations. Gender comparisons were conducted using group statistics, while bootstrap analysis with 1,000 resamples ensured robust estimates and confidence intervals. Results show that students experienced a moderate to high level of insecurity, with notable gender differences. Female students consistently reported higher insecurity than males in key areas such as fear of kidnapping (Male: M = 1.61; Female: M = 3.22), terrorism threats (Male: M = 1.81; Female: M = 3.09), and community insecurity affecting academic focus (Male: M = 1.52; Female: M = 2.81). Both genders reported high insecurity related to cult activities (Male: M = 3.42; Female: M = 3.54), night-time movement on campus (Male: M = 3.05; Female: M = 3.32), and inadequate security patrols (Male: M = 3.32; Female: M = 3.19), indicating widespread insecurity across tertiary institutions. The study concluded that enhancing campus security and fostering supportive school environments are vital for safeguarding students’ psychological well-being and improving academic focus.